Emotions in politics the affect dimension in political tension - Demertzis, Nicolas; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Prompted by the'affective turn' within the entire spectrum of the social sciences, this books brings together the twin disciplines of political psychology and the political sociology of emotions to explore the complex relationship between politics and emotion at both the mass and individual level with special focus on cases of political tension.
Keywords: Science; Science; Science, general